(untitled) (Current Horticulture, 2024)
Garlic (Allium sativum L.) is one of the important spices crops that required on daily basis in kitchens and cuisines across the world. Scape or flowering stalk induction is highly important for crop improvement as garlic is a vegetatively propagated crop. However, scape formation has not achieved yet by any means. Meristems (0.1- 0.3 mm) of garlic cv. Bhima Purple were cultured in vitro on basal MS medium fortified with 0.1 mgl–1 NAA, 1.0 mgl–1 Kinetin and 3% sucrose (w/v). Proliferated meristems (mericlones) were sub-cultured after 10-15 days. About 55-60 days old cultures were sub-cultured on MS + 1 mgl–1 Kinetin + 6% sucrose in liquid medium for microbulbil induction and maintained till its harvest. Microbulbils were induced on mericlones after about 70-75 days after initial inoculation. In vitro induced bulbils transformed into a small garlic bulb having 2-3 cloves or microbulbils after 110-115 days of initial culturing. Subsequently after 125-130 days the maiden in-vitro scape formation was observed. It showed a ray of light to use this alternative strategy, i.e. in-vitro scape induction to induce flowering stalk in garlic. Also, the successful in-vitro bulb development reported first time herein would give an opportunity of mass production of garlic without managing cumbersome field propagations.